Workshop on s-claim application system for BPJS claim officers at Grandmed Lubuk Pakam Hospital - Purba, Okto Hebron; Yuanita, Ratna (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
BPJS Health is a public legal entity that is directly responsible to the President and functions to organize health insurance programs for all Indonesian residents, including foreigners who work for a minimum of six months in Indonesia. The BPJS Health claim procedure can be quite complicated and requires a lot of supporting documents. Unclearness in the guidance or instructions provided can make participants confused and not prepare the complete documents required, one of which is incomplete data files. This is a problem that slows down the claim process. This activity aims to provide health education on the application of the S-National Health Insurance (JKN) system, namely health protection program in Indonesia designed to provide basic health care and protection benefits for all Indonesian citizens. The main goal of JKN is to ensure that everyone in Indonesia has access to adequate basic health services, either through contributions paid by participants themselves or contributions paid by the government for certain groups. With the existence of JKN, it is hoped that the entire population of Indonesia can feel the benefits of equitable and quality health services, thereby improving the health status of the community as a whole. Claims to BPJS officers. The method of implementing activities is using observation sheets and questionnaires regarding the application of the S-Claim system to BPJS officers. Through this activity, it is hoped that the knowledge of BPJS claims officers can increase and change attitudes so that they can apply the BPJS E-Claim system correctly. Socialization to BPJS claims officers can be concluded that the knowledge of BPJS claims officers at Grandmed Lubuk Pakam Hospital has increased by 60% after conducting socialization using discussion, lecture and question and answer methods as well as holding quizzes or tests to evaluate participants' understanding of the S application.